Exclusión social, política criminal y culpabilidad penal en el Perú: una reinterpretación del artículo 15 del Código Penal - Chanjan Documet, Rafael (Pontificia Universidad Católica del Perú, 2025)
The permanent situation of social exclusion experienced by some people in Peru requires that the criminal system give them special treatment for certain criminal acts in order to implement a criminal policy in accordance with a Social and Democratic State of Law. This paper critically analyzes the current Peruvian criminal policy model, which has a punitive or “soft hand” treatment depending the type of crime, and which tends to perpetuate and aggravate the situation of social exclusion of some groups, not significantly reducing crime rates. Therefore, a reflection is proposed on the dogmatic category of culpability, specifically exigibility, in order to exonerate or reduce the criminal responsibility of these people for certain types of crimes, reinterpreting article 15 of the Peruvian Criminal Code.

Es necesario primero diseñar e implementar una política criminal adecuada a los principios de un Estado Social y Democrático de Derecho, para que, en ese marco, el sistema penal pueda otorgar un tratamiento especial a las personas en situación de exclusión social. El presente trabajo aborda críticamente el actual modelo de política criminal peruano, el cual tiene un corte punitivista o de “mano blanda” según el tipo de delito, y que tiende a perpetuar y agravar la situación de exclusión social de ciertos colectivos, por lo que no ha logrado disminuir significativamente las tasas de criminalidad. Por ende, se plantea una reflexión de la categoría dogmática de la culpabilidad, en específico la exigibilidad, a fin de que se pueda exculpar o disminuir la responsabilidad penal de estas personas ante cierto tipo de delitos, reinterpretando el artículo 15 del Código Penal peruano.
Social exclusion, criminal policy and criminal responsibility in Peru: a reinterpretation of article 15 of the criminal code
Keywords: Social exclusion; Peruvian criminal policy; Criminal; Culpability; Perú; Exclusión social; Política criminal peruana; Culpabilidad penal; Derecho Penal; Perú; https://purl.org/pe-repo/ocde/ford#5.05.00